PENGARUH PENYULUHAN AGAMA DAN PENYULUHAN KESEHATAN DENGAN METODE VISUAL TERHADAP SIKAP PASANGAN SEJENIS DI LEMBAGA PEMASYARAKATAN KLAS II B ANAK WANITA TANGERANG - Ida Faridah; Fitriyanti Fitriyanti (Jurnal Kesehatan, 2018)
Background: The results of the initial observations of the author by conducting direct interviews with 5 inmates in the Class II B Correctional Institution of Tangerang Women Children, it is known that there are frequent sexual deviations committed by the prisoners. Whether done by coercion or done with the will of the inmates themselves. Objective: from this study was to determine the effect of health counseling and religious counseling with visual methods on attitudes of LGBT couples in Class II B Correctional Institution Tangerang Girls' Children. This type of research is: quantitative research and quantitative research and the method used is quasi experimental design, with the design of Two Group Pretest-Posttest design. The number of samples in this study were 60 inmates in Class II B Correctional Institutions for Girls who were divided into two groups. Groups that are given religious counseling and groups given health education. The results of the study: about the influence of religious counseling and health education with visual methods on attitudes of LGBT couples in Correctional Institutions Class II B Tangerang Girls concluded that the attitude of respondents to LGBT after being given intervention (posttest) in group I (intervention with religious counseling) increased 4,700 and in group II (intervention with health counseling) increased by 1,100. Suggestion: health workers in Correctional Institutions are more spiritually approaching inmates and improve the quality and quantity of health counseling about LGBT behavior from the health side so that inmates understand the dangers of LGBT behavior in all aspects.